Experimental Investigation into the Mechanisms of Liquid-Phase Damage in Shale Oil Reservoirs: A Case Study from the Leijia Area - Tuan Gu; Chenglong Ma; Yugang Li; Feng Zhao; Xiaoxiang Wang; Jinze Xu (Energies)
The fourth member of the Shahejie Formation in the Leijia area of the western depression of the Liaohe Oilfield represents a typical shale oil reservoir. However, post-hydraulic fracturing operations in this region are often hindered by significant discrepancies in well productivity, low fracturing fluid flowback efficiency, and an unclear understanding of reservoir damage mechanisms during fracturing. These challenges have become major bottlenecks restricting the efficient exploration and development of shale oil in this block. In this study, a series of laboratory-simulated experiments were conducted to investigate the primary mechanisms of formation damage induced by fracturing fluids in shale oil reservoirs. An experimental methodology for evaluating reservoir damage caused by fracturing fluids was developed accordingly. Results indicate that guar gum-based fracturing fluids exhibit good compatibility with formation-sensitive minerals, resulting in relatively minor damage. In contrast, capillary trapping of the aqueous phase leads to moderate damage, while polymer adsorption and retention cause low to moderate impairment. The damage associated with fracturing fluid invasion into fractures is found to be moderately high. Overall, the dominant damage mechanisms of guar gum fracturing fluids in the Shahejie Member 4 shale oil reservoir are identified as aqueous phase trapping and polymer adsorption. Based on the identified damage mechanisms, corresponding optimization strategies for fracturing fluid formulations are proposed. The findings of this research provide critical insights for improving shale oil development strategies in the Leijia area.